Mystery Shopping for Consumer Contentment, Reliance, and Adhesion in the Retail Industry: A Descriptive Study - Bhattacharya, Sourabh; Mishra, Bibhuti Bhusan; Mishra, Uma Sankar (Indian Journal of Marketing, 2015)
Mystery shopping plays a crucial role in ascertaining service standards in the organized retail industry. At the present juncture, when products are same, discount rates are same on the same prices across formats; hence, service standards act as the biggest differentiator for positioning a retail brand. Department stores like Pantaloon, Westside, Saks Fifth Avenue, Zara, H&M are bringing in more and more value additions in the service quality chain of the customer ; whereas, the hypermarkets and cash&carry stores like Star India Bazaar, Shoprite Hyper, Metro AG, Bharti-Walmart have found that price and variety are no longer the greatest differentiators ; rather, service standards are playing as the greatest differentiators. Under these circumstances, through independent, impartial mystery researchers, mystery shopping can play as the greatest differentiator. Through extensive literature review, this paper attempted to understand the different nuances of mystery shopping and how its advantages can be exploited to the fullest extent for retail companies.